The Evolution of Street art and Graffiti in India - Bhasin, Aparajita (Street Art & Urban Creativity, 2018)
This working essay attempts to trace the history of art making in the public space in India. This is important for understanding the evolutionary process of the local graffiti and street art culture and the organisation of many street art festivals across the country. This festival structure often leads to a collaboration with various government bodies in order to work within a city or a neighbourhood to create a large scale immersive experience. This essay will try to argue the importance of people in the creation and evaluation of street art while collaborating and negotiating with various government institutions.